ELUCIDATION OF THE ELECTRONIC SPECTRUM CHANGES OF KA-Al3+ COMPLEX BY POTENTIOMETRIC TITRATION, FTIR, 13C RMN AND QUANTUM MECHANICS - Mário S. Piantavini; Alan G. Gonçalves; Ângela C. L. B. Trindade; Miguel D. Noseda; Ana L. R. Mercê; Antonio E. H. Machado; Roberto Pontarolo (Química Nova)
Kojic acid (KA) is an organic acid widely used in pharmaceutical industry, mainly as a skin lightening agent. Based on the ability of KA to form complexes with ions, we found the most possible kind of complex formed with cation aluminum. KA-Al3+ complex structures were studied using potentiometric and spectrophotometric (UV) titrations, FTIR and 13C NMR. The electronic spectroscopy showed that the KA-Al3+ complexes absorb at higher wavelengths (λmax= 305 nm) than do the non-complexed KA (λmax= 269 nm), confirming complexation. The IR spectra of KA complexed and not complexed allowed us to correlate the changes in the absorption of enol and carbonyl groups in absence and presence of Al3+ in aqueous solutions. The complexation suggested by the potentiometric titration and FTIR spectroscopy are in accordance with the data obtained from NMR results. Calculations based on quantum mechanics were utilized to understand the differences found in the noncomplexed and complexed KAH electronic spectra